2017
DOI: 10.1111/trf.14188
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of red blood cells from donors exhibiting high hemolysis demonstrates a reduction in membrane‐associated proteins involved in the oxidative response

Abstract: BACKGROUND The development of hemolysis during ex vivo hypothermic storage is multifaceted. Standardization of collection and production processes is used to minimize variability in biologics manufacturing and to maximize product quality. However, the influence of various donor characteristics on product quality is often difficult to evaluate and to control. Using a proteomic approach, we aimed to decipher relevant donor characteristics that may predict red blood cell (RBC) quality during storage. STUDY DESIGN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 42 publications
(71 reference statements)
1
12
0
Order By: Relevance
“…It has been hypothesized that transfusion of RBCs with extended storage durations may be associated with an increased risk of cardiovascular events, multiorgan failure, and mortality in susceptible transfusion recipients, although this has not borne out in a series of randomized control trials . Studies of RBC recovery and survival after cold storage have demonstrated variability among donors that is reproducible over time in both human studies and murine models . These studies have suggested that the propensity of RBCs to hemolyze under stress, including cold storage, is heritable and that the intrinsic rate of hemolysis in vitro and in vivo is stable within individuals over time but highly variable among individuals and among different demographic subgroups .…”
mentioning
confidence: 99%
“…It has been hypothesized that transfusion of RBCs with extended storage durations may be associated with an increased risk of cardiovascular events, multiorgan failure, and mortality in susceptible transfusion recipients, although this has not borne out in a series of randomized control trials . Studies of RBC recovery and survival after cold storage have demonstrated variability among donors that is reproducible over time in both human studies and murine models . These studies have suggested that the propensity of RBCs to hemolyze under stress, including cold storage, is heritable and that the intrinsic rate of hemolysis in vitro and in vivo is stable within individuals over time but highly variable among individuals and among different demographic subgroups .…”
mentioning
confidence: 99%
“…For instance, the osmotic fragility of CPDA-stored RBCs has a correlation with the levels of in-bag hemolysis, but, in quantity terms, fragility can reveal no more than 11% of its variation ( 42 ). Moreover, stored RBCs from G6PD + donors that repeatedly exhibit high in-bag hemolysis at outdate are also characterized by reduced ability to resist osmotic stress compared to those exhibiting normal hemolysis ( 49 ). In a similar way, in-bag hemolysis in G6PD − units had a positive correlation with the baseline levels of osmotic hemolysis at body temperature (Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…The redox activity of RBCs, which contain a strongly oxidizing cytoplasm, governs their lifetime in circulation ( 51 , 52 ), and thus, changes in the antioxidant activity during storage ( 53 ) may have a substantial effect on pre- and post-storage viability. Quantitative proteomics analyses have identified a number of proteins in the supernatant of RBC units showing linear correlations with the absolute levels of extracellular Hb ( 54 ), while the donor-related susceptibility of stored RBCs to hemolysis was associated with modifications in RBC membrane proteins involved in oxidative response pathways and decreased storage levels of 2,3-BPG ( 49 ). The present study in G6PD − RBCs, which are more susceptible to metabolic changes and protein oxidation compared to normal cells ( 22 , 24 ), further revealed the strong interplay of in-bag hemolysis and donor biology, since, for instance, RBC protein oxidation at baseline had positive correlations with both in-bag and mechanical hemolysis at body temperature (Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, even within the subgroup of glucose 6‐phosphate dehydrogenase deficiency donors, variability was seen that impacted the storage quality of RBCs, indicating the complexity of donor‐related factors on the RBC storage lesion. Another study of the membrane proteome of 10 donors whose RBC units exhibited repeated high hemolysis at outdate demonstrated marked reduction in candidate membrane protein levels involved in oxidative defense at baseline, suggesting that these proteins may be predictive of storage quality and potentially useful as a screening tool . Finally, two REDS‐III (Recipient Epidemiology and Donor Evaluation Study) RBC‐Omics studies have evaluated the effects of donor demographics and metabolism on RBC storage and hemolysis (Table ) and future studies may permit further analysis of how donor characteristics impact recipient outcomes.…”
Section: Big Data Applications and Omics Studies In Transfusion Medicinementioning
confidence: 99%
“…Another study of the membrane proteome of 10 donors whose RBC units exhibited repeated high hemolysis at outdate demonstrated marked reduction in candidate membrane protein levels involved in oxidative defense at baseline, suggesting that these proteins may be predictive of storage quality and potentially useful as a screening tool. 21 Finally, two REDS-III (Recipient Epidemiology and Donor Evaluation Study) RBC-Omics studies 22,23 have evaluated the effects of donor demographics and metabolism on RBC storage and hemolysis (Table 2) and future studies may permit further analysis of how donor characteristics impact recipient outcomes. Notably, RBC-Omics data will be publicly available at the conclusion of the REDS-III program in March 2019.…”
Section: Big Data and Donor Characteristicsmentioning
confidence: 99%